2023
DOI: 10.1136/openhrt-2022-002222
|View full text |Cite
|
Sign up to set email alerts
|

Association of Life’s Simple 7 and ideal cardiovascular health in American Indians/Alaska Natives

Abstract: ObjectiveAmerican Indians and Alaska Natives (AI/ANs) are an understudied population at high risk for cardiovascular diseases (CVDs); little is known about contextual factors contributing to CVDs in AI/ANs. This study examined the association of Life’s Simple 7 (LS7) factors and social determinants of health (SDH) with CVD outcomes in a nationally representative sample of AI/ANs.MethodsWe conducted a cross-sectional study of 8497 AI/ANs using 2017 Behavioural Risk Factor Surveillance Survey data. Individual LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Worldwide, factors are similar, although inequalities in health access between populations have been described [ 344 346 ], and several studies have shown that diagnosis, control and treatment of hypertension are worse in rural areas than in urban areas [ 347 ]. Indigenous populations worldwide experience a huge gap in access to general health and health treatments and mortality [ 348 ], including CVD and diabetes [ 347 , 349 , 350 ]. This divide is observed as a combination of racial discrimination, poverty, lifestyle and access to services due to geographical isolation [ 348 , 351 ].…”
Section: Holistic Approach To Blood Pressure Prevention Across the Globementioning
confidence: 99%
“…Worldwide, factors are similar, although inequalities in health access between populations have been described [ 344 346 ], and several studies have shown that diagnosis, control and treatment of hypertension are worse in rural areas than in urban areas [ 347 ]. Indigenous populations worldwide experience a huge gap in access to general health and health treatments and mortality [ 348 ], including CVD and diabetes [ 347 , 349 , 350 ]. This divide is observed as a combination of racial discrimination, poverty, lifestyle and access to services due to geographical isolation [ 348 , 351 ].…”
Section: Holistic Approach To Blood Pressure Prevention Across the Globementioning
confidence: 99%